2015
DOI: 10.1118/1.4921807
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric results in treatments of neuroblastoma and neuroendocrine tumors with 131I‐metaiodobenzylguanidine with implications for the activity to administer

Abstract: Dosimetric results in treatments of neuroblastoma and neuroendocrine tumors with (131)I-metaiodobenzylguanidine with implications for the activity to administer.MINGUEZ GABINA, PABLO; Flux, Glenn; Genolla, Jose; Guayambuco, Sonia; Delgado, Alejandro; Fombellida, Jose Cruz; Sjögreen Gleisner, Katarina , Flux, G., Genolla, J., Guayambuco, S., Delgado, A., Fombellida, J. C., & Sjögreen Gleisner, K. (2015). Dosimetric results in treatments of neuroblastoma and neuroendocrine tumors with (131)I-metaiodobenzylguan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 44 publications
3
8
2
Order By: Relevance
“…Furthermore, we found trends to suggest correlations between both MYCN amplification and relative Curie score. In contrast to our hypothesis and results of previous studies, we did not find a significant correlation between WBD and response or toxicity …”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Furthermore, we found trends to suggest correlations between both MYCN amplification and relative Curie score. In contrast to our hypothesis and results of previous studies, we did not find a significant correlation between WBD and response or toxicity …”
Section: Discussioncontrasting
confidence: 99%
“…To account for this, we conducted a subanalysis of MIBG monotherapy protocols and again no significant association was observed. A recent study also found no correlation between grade of hematologic toxicity and WBD, but they suggested that the lack of correlation might be attributed to small sample size, wide age variance, or prior hematotoxic treatments . One possible explanation for the low correlation in our study is the narrow range of WBD.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…The patient mass was 63 kg, which according to the protocol by Gaze et al (2005) implied an administered activity of 28 GBq for the first administration, and assuming that the whole-body absorbed dose would be close to 2 Gy (Minguez et al, 2015), another 28 GBq for the second administration. However, since the maximum authorised 131 I activity at the Gurutzeta-Cruces University Hospital is 14.8 GBq, a modification of the schedule was necessary.…”
Section: Introductionmentioning
confidence: 99%